Pengaruh Kompetensi Dan Prestasi Kerja Terhadap Promosi jabatan Karyawan Pada PT Tor Ganda Medan - Novia Eka Yulyanti Gea; M. Safi Murad Daulay (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2021)
The purpuse of this study is to determine the effect of competence on employee promotion at PT. Tor Ganda Medan, to determine the effect of job performance on employee promotion at PT. Tor Ganda Medan and to determine the effect of competencee and work performance simultaneously on employee promotion at PT. Tor Ganda Medan. This research is a quantitative descriptive study with a questionnaire instrument carried out at PT. Ganda Medan. The population in this study were employees of PT. Ganda Medan as many as 85 people by using total sambling the size of the resarch sample is as many as 85 people. The results showed that the tcount Competence value was 2.268 and the ttable value was 1.988 with the provisions that the tcount value > ttable and sigcount < sigtable or (2,268 > 1,988) and (0.026 < 0.05), the tcount value of work performance was 6.246 and the ttable value was 1.988 with the provisions of the value of tcount > ttable and sighitung < sigtabel or (6.246 > 1.988 ) and (0.000 < 0.05) and the Fcount value of the Competence and Work Performance variable is 37.347 and the ttable value is 2.711 with the provisions of the value of Fcount > Ftable and sigcount < sigtable or ( 37.347 > 2.711) and (0.000 < 0.05). The conclusion of the study is that competence has a significant effect on employee promotion at PT Tor Ganda Medan, work performance has a significant effect on job promotion and is the dominant variable in employee promotion at PT Tor Ganda Medan and simultaneously Competence and work performance have a significant effect on employee promotions at PT Tor Ganda Medan.